2021
DOI: 10.1051/0004-6361/202141057
|View full text |Cite
|
Sign up to set email alerts
|

A major asymmetric ice trap in a planet-forming disk

Abstract: Gas-phase sulphur-bearing volatiles appear to be severely depleted in protoplanetary disks. The detection of CS and the non-detections of SO and SO2 in many disks have shown that the gas in the warm molecular layer, where giant planets accrete their atmospheres, has a high C/O ratio. In this Letter, we report the detection of SO and SO2 in the Oph-IRS 48 disk using ALMA. This is the first case of prominent SO2 emission detected from a protoplanetary disk. The molecular emissions of both molecules is spatially … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 58 publications
5
30
1
Order By: Relevance
“…Considering the reported rms level of 1.2 mJy bm −1 channel −1 with a channel width of 1.6 km s −1 , a line width of ∼14 km s −1 and a beam size of 0.63×0.50" (van der Marel et al 2021), we compute a 3σ upper limit on the C 2 H flux density of 11 mJy bm −1 km s −1 , or a scaled T b,peak,100pc limit of <1.1 K km s −1 . Such a low value of C 2 H is consistent with the low CS/SO ratio reported by Booth et al (2021a).…”
Section: Appendix A: Icy Dust Mass Calculationsupporting
confidence: 91%
See 1 more Smart Citation
“…Considering the reported rms level of 1.2 mJy bm −1 channel −1 with a channel width of 1.6 km s −1 , a line width of ∼14 km s −1 and a beam size of 0.63×0.50" (van der Marel et al 2021), we compute a 3σ upper limit on the C 2 H flux density of 11 mJy bm −1 km s −1 , or a scaled T b,peak,100pc limit of <1.1 K km s −1 . Such a low value of C 2 H is consistent with the low CS/SO ratio reported by Booth et al (2021a).…”
Section: Appendix A: Icy Dust Mass Calculationsupporting
confidence: 91%
“…Current disk surveys of C/O tracers such as C 2 H (Bergin et al 2016;Semenov et al 2018;Cleeves et al 2018) appear to show a bimodal distribution of disks with and without C 2 H detection indicating either high (C/O>1) or low (C/O<1) ratios (Bergner et al 2019;Miotello et al 2019) but it is unclear whether this bimodality is an intrinsic property or the result of physical-chemical processes. The recent discovery of low C/O at the location of the asymmetric Oph IRS 48 dust trap (Booth et al 2021a) suggests that pressure bumps may play a key role in regulating the C/O profile in disks, which is particularly relevant considering that pressure bumps are usually associated with giant planets (e.g. Pinilla et al 2012b;van der Marel et al 2016) and those planets would accrete the composition of the gaseous material at the bump location.…”
Section: Introductionmentioning
confidence: 99%
“…The emission from these regions may also be related to the action of inner jets and outflow (e.g., Podio et al 2021) or to the innermost regions of disk and envelope (e.g., Harsono et al 2021) where dust mantles can sublimate, thus resembling a hot-corino chemistry. Booth et al (2021) also showed an asymmetric SO and SO 2 emission co-spatial with a dust crescent where the molecular enhancement would be related to the sublimation of ices at the edge of a dust cavity at a separation of ∼50 au. However, in the case of HL Tau presented here, a further explanation is possible.…”
Section: Origin Of the So And So 2 Emissionmentioning
confidence: 90%
“…We note that H 2 CS was detected in MWC 480 (Le Gal et al 2019), and H 2 S was detected in GG Tau (Phuong et al 2018) and in four protoplanetary disks in Taurus (Rivière-Marichalar et al 2021). Furthermore, SO has been detected in a few PPDs (Pacheco-Vázquez et al 2016;Booth et al 2018Booth et al , 2021Le Gal et al 2021), and SO 2 has been observed toward IRS 48 as well (Booth et al 2021). Recently, CCS was detected toward GG Tau (Phuong et al 2021), but the low signal-to-noise ratio (s/n) precluded the analysis of the spatial distribution.…”
Section: Introductionmentioning
confidence: 99%